2018
DOI: 10.2147/tacg.s153469
|View full text |Cite
|
Sign up to set email alerts
|

Tetrasomy 18p: case report and review of literature

Abstract: Tetrasomy 18p syndrome (Online Mendelian Inheritance in Man 614290) is a very rare chromosomal disorder that is caused by the presence of isochromosome 18p, which is a supernumerary marker composed of two copies of the p arm of chromosome 18. Most tetrasomy 18p cases are de novo cases; however, familial cases have also been reported. It is characterized mainly by developmental delays, cognitive impairment, hypotonia, typical dysmorphic features, and other anomalies. Herein, we report de novo tetrasomy 18p in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…NGS showed that they had the genotype dup(18)(p11.32→p11.21)×4. It has been reported that the clinical symptoms are likely isochromosome 18p [i(18p)] syndromes or tetrasomy 18p syndrome, which feature neonatal feeding problems, hypoevolutism, and high risk of infections [ 5 , 6 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NGS showed that they had the genotype dup(18)(p11.32→p11.21)×4. It has been reported that the clinical symptoms are likely isochromosome 18p [i(18p)] syndromes or tetrasomy 18p syndrome, which feature neonatal feeding problems, hypoevolutism, and high risk of infections [ 5 , 6 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…There may be a hot breakpoint located at 18(p11.21). In region 18p, approximately 67 genes can contribute to the phenotypes, including AFG3L2, MC2R, and TGIF1, which are associated with developmental disorders [5,6]. So, when taking care of patient 61259, pay attention to artificial feeding, avoiding infections, and evaluating affected organs and systems.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of tetrasomy 18p is 1/140,000 in live newborns [22], which is the most common type among all these isochromosomes [23]. Their clinical characteristics include moderate to severe intellectual disability, developmental delay, microcephaly, typical dysmorphic features, and other anomalies, such as muscle tone abnormalities [24,25]. Cat eye syndrome (CES) is a rare developmental disorder with an incidence of 1/150,000 to 1/50,000 in liveborn infants [26].…”
Section: Discussionmentioning
confidence: 99%
“…In absence of (rare) malformations, a prenatal ultrasound diagnosis is very difficult because the only prenatal sign could be aspecific growth retardation. For this reason, without an invasive test, most cases are detected after birth …”
Section: Discussionmentioning
confidence: 99%